History in the View of the Principle of Universal Relationship of Phenomena - Krakauskas, Edmundas (Problemos, 1986)
In the article the materialistic-dialectical conception of the principle of universal relationship of phenomena is defined, its difference from idealistic and metaphysical ones is pointed out, and, finally, the significance of application of the principle in historical sciences is revealed. History does not mean only that, what is recorded and what is already known. History means all that, what has occurred, and what now determines the development of society. History means, after all, a kind of interrelation, a kind of interaction between social (material as well as spiritual) and natural phenomena. An investigation into the history of all nations of the world is a prerequisite of a deeper insight into the histories of particular nations as well as into the regularities of development of mankind.